Description of Throat Pain in Post-General Anesthesia Patients with Endotracheal Tube at dr. Soedirman Hospital, Kebumen, in 2023 - Nistiani, Mia; Wibowo, Tophan Heri; Siwi, Adiratna Sekar (Viva Medika, 2023)
Complications that many respondents complained about after surgery with general anesthesia, namely Post-Operative Sore Throat (POST). Post-surgery sore throat is a minor complication that occurs in ETT intubated patients and results in dysphonia, dysphagia and odynophagia. In Indonesia, 20%–60% of respondents complain of sore throat after surgery with GA-ETT. The purpose of this study was to see the description of post-general anesthesia sore throat with ETT at Dr. Soedirman Kebumen. The design of this study is a descriptive cross-sectional approach using the POST instrument. The research was conducted from March to April 2023 in the recovery room with 50 respondents. Data collection by accidental sampling and analyzed using univariate test. The results of the study showed that many respondents did not experience throat pain, totaling 20 respondents (40%) and complaining that the most complaints were mild pain, amounting to 17 respondents (34%). This study shows that the majority of patients only complain of mild pain and no sore throat. So after ETT intubation at Dr. Soedirman Kebumen can minimize the level of sore throat.